(untitled) (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2014)
The association between serum uric acid and ischemic heart disease remains controversial and it has been difficult to identify the specific role of elevated serum uric acid because of its association with established cardiovascular risk factors such as hypertension, diabetes mellitus, hyperlipidaemia and obesity. Our objective was to study the association of serum uric acid level with confirmed cases of Acute Coronary Syndrome i.e. Unstable Angina, Acute Myocardial Infarction(AMI). The study was conducted in Chittagong Medical College (CMC) & University of Science and Technology(USTC) and nearby diagnostic centre. The study was based on Patients with Acute Coronary Syndrome proved by ECG and/or raised serum Troponin I. The aim of the study was to determine the relationship between serum uric acid and Unstable angina or myocardial infacrtion. There were 35% males & 5% females. The mean age of respondent was 50 years and age ranges from 35 to 70 years. In this study 50 cases of diagnosed myocardial infarction were selected and subsequently investigated with ECG, Radiological and Echocardiographic investigations. Increased serum uric acid levels are a common finding in patients with high blood pressure, insulin resistance, obesity and Cardiovascular disease. The clinical findings, chest X-ray and ECG findings of patients with risk factors for myocardial infarction were extensively studied and the findings are consistent with findings stated in textbooks. DOI: http://dx.doi.org/10.3329/cmoshmcj.v13i2.21070